The Impact Of Social Media Marketing Features On Consumer Purchasing Decisions In The Skin Care Industry: Brand Trust As A Mediator - Irfan Indrajaya, Ahmad; Reegia Aulia Putri, Rasheesa; Dian Nita, Selvy (Journal of Exploratory Dynamic Problems, 2024)
Social media has changed the way brands communicate. As we currently know, the majority of types of businesses, from small, medium to large scale, are changing their approach to gain interest from the target market segment. This research aims to: (1) determine the influence of social media marketing on consumer purchasing decisions. (2) knowing the influence of social media marketing on consumer purchasing decisions, (3) knowing the influence of brand trust on consumer purchasing decisions, (4) knowing the influence of social media marketing on consumer purchasing decisions through brand trust as a mediator. This research uses quantitative methods with a descriptive approach. The analytical method used is Structural Equation Modeling (SEM) with Smart PLS. The sampling technique uses the Accidental sampling method by taking samples via the Google Form Questionnaire which is distributed online. Samples were distributed to 200 respondents according to research criteria. From this research, the results obtained are (1) social media marketing has a positive and significant effect on consumer purchasing decisions, (2) social media marketing has a positive and significant effect on consumer purchasing decisions, (3) brand trust has a positive and significant effect on consumer purchasing decisions, (4) social media marketing has a positive and significant effect on consumer purchasing decisions through brand trust as a mediator.